Genetic diversity analysis of chicken breeds of India - Tantia, M S; Vijh, R K; Kumar, S T Bharani; Mishra, Bina; Ahlawat, S P S (The Indian Journal of Animal Sciences, 2011)
India has 15 defined chicken breeds distributed in various parts of the country. These breeds are well adapted and intricately associated with the culture of farming community. Highly polymorphic ubiquitously distributed 25 microsatellite loci were utilized for genotyping these breeds to establish population parameters and genetic relationship among them. All the loci selected exhibited high polymorphic information content and gene diversity. All the breeds also revealed high degree of gene diversity. The F statistics points towards presence of population structure in all the chicken breeds and there was significant differentiation among the chicken populations. The chord genetic distance topology using neighbour joining algorithm established 8 distinct clusters based on bootstrap values obtained from 1000 replicates. Except for Nicobari and Punjab Brown breeds all the chicken breeds conformed to their respective geographical locations. Â